Loyalitas Konsumen: Implikasi dari Diferensiasi Produk dan Nilai Emosional - Dita Amanah; Dedy Ansari Harahap (JURNAL ILMIAH MANAJEMEN & BISNIS, 2019)
The purpose of this research is to analyze the role of product differentiation and emotional value on consumer loyalty in Lazada Indonesia. The sample in this study amounted to 150 students of the Faculty of Economics and Business, Universitas Pendidikan Indonesia with purposive sampling as a sampling technique. They are students who shop online more than twice at Lazada. Partially product differentiation has no effect on student loyalty, emotional value has a significant effect on student loyalty. Simultaneously product differentiation and emotional value simultaneously have a significant influence on student loyalty to Lazada Indonesia, the ability of product differentiation and emotional value to explain student loyalty to Lazada Indonesia is very limited.